2003
DOI: 10.1093/sleep/26.8.943
|View full text |Cite
|
Sign up to set email alerts
|

Anandamide Enhances Extracellular Levels of Adenosine and Induces Sleep: An In Vivo Microdialysis Study

Abstract: Anandamide increased adenosine levels in the basal forebrain and also increased sleep. The soporific effects of anandamide were mediated by the CB1 receptor, since the effects were blocked by the CB1-receptor antagonist. These findings identify a potential therapeutic use of endocannabinoids to induce sleep in conditions where sleep may be severely attenuated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
59
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(64 citation statements)
references
References 39 publications
5
59
0
Order By: Relevance
“…The endocannabinoid system is also involved in the mechanisms of sleep regulation [25][26][27]. For Editorial Neurobiology of suicidal behavior in post-traumatic stress disorder example, it has been reported that the endocannabinoid anandamide increased adenosine in the basal forebrain and increased sleep [27]. Sleep abnormalities and other symptoms of PTSD may contribute to increased suicidality in PTSD patients [28].…”
Section: Leo Shermentioning
confidence: 99%
“…The endocannabinoid system is also involved in the mechanisms of sleep regulation [25][26][27]. For Editorial Neurobiology of suicidal behavior in post-traumatic stress disorder example, it has been reported that the endocannabinoid anandamide increased adenosine in the basal forebrain and increased sleep [27]. Sleep abnormalities and other symptoms of PTSD may contribute to increased suicidality in PTSD patients [28].…”
Section: Leo Shermentioning
confidence: 99%
“…73 Endogenous cannabinoids increase adenosine and thus promote sleep. 74 In a study of the effects of cannabis extract on sleep in young adults, Nicholson and colleagues 75 found that administration of 15 mg of d-9-tetrahydrocannabinol (THC) caused decreased sleep latency, increased sleepiness, and impaired memory, and it also resulted in mood changes the next day. THC also has been shown to decrease REM sleep.…”
Section: Illicit Drugs and Other Substances Of Abuse Marijuanamentioning
confidence: 99%
“…Cannabinoids may even prevent AD pathology as CB 1 agonists have been shown to block microglial activation in vivo (Ramirez et al 2005). Animal models suggest that CB 1 receptor agonists may have a positive effect on sleep architecture (Murillo-Rodriguez et al 2003). CB 1 receptor agonists are currently used in the treatment of Tourette's syndrome (Muller-Vahl et al 2003a,b), multiple sclerosis (Svendsen et al 2004), pain , and nausea in patients receiving chemotherapy .…”
Section: Introductionmentioning
confidence: 99%